The Square-Plus Flap: A Modification to Release Long Postburn Scar Contractures - Hifny, Mahmoud A.; Ogawa, Rei (Archives of Plastic Surgery, 2024)
The square flap method has been successful in releasing contracture bands at various body regions. However, the original square flap method alone may not be efficient in releasing long contracture bands. We, therefore, proposed an extended design to the traditional design, which is called the “square-plus flap.” A 4-year-old girl presented with a postburn web-like contracture band over the right axilla. We marked a square flap technique at the center of the contracture band and then two additional Z-plasties were placed on both edges of the flap. After the release and securing of the square flap, the adjacent distal Z-plasty was then transposed and sutured in their new locations. We do not need to incise the proximal Z-plasty as we could achieve complete relaxation of the contracture band. This novel modification can be added to the plastic surgeon's armamentarium for releasing long postburn contracture bands involving distinct body regions.
Keywords: square flap; Z-plasty; burn; contractures; scar